LEARNING STRATEGIES FOR STUDENTS WITH DIFFICULTY LEARNING MATHEMATICS (DISCALCULIA) IN CLASS XI - Rostien Puput Anggoro; Idha Atmim Umurona (Universitas Ahmad Dahlan, 2019)
This study aims to describe the learning strategies in learning approaches and learning methods and the impact of using these learning strategies for dyscalculia students in class XI of State Special Need School (SLBN) Tamanwinagun Kebumen in the 2018/2019 academic year. The subject of this study was a student of class XI Sate Special School (SLBN) Tamanwinagun Kebumen in the 2018/2019 academic year with the source of research data, namely a classroom teacher. This research's object is the mathematics learning strategy for students having difficulty learning mathematics (dyscalculia). Data collection techniques in the form of observation, interviews, tests, and documentation. The data analysis used an interactive model from Miles and Huberman, which describes conditions or phenomena as they are. The research conducted by researchers used a qualitative approach with a study design at SLBN Tamanwinangun Kebumen. The results showed that the teacher's learning strategies for dyscalculia consisted of learning approaches and methods. The learning approach includes a contextual approach, and an individual approach with an approach suitable for students is a contextual approach. The learning methods used include the lecture method, the question and answer method, the assignment method, and the visual method. The appropriate learning method for students is the visual method. The application of learning strategies in the form of approaches and methods used by the teacher in overcoming student dyscalculia impacts learning mathematics. This impact can be seen from the cognitive aspects of the students with dyscalculia, including memory, understanding, application, analysis, evaluation.